(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Cloud computing has changed the whole picture that distributed computing used to present such asÂ Grid computing, server client computing. Despite Cloud offers great benefits, it also introduces a myriad of security threats to the information and data which is now being ported from on-premises to off-premises. These security threats must be overcome in order to get full benefit from this new computing exemplar. This paper identifies the importance of awareness behaviour in context of information security for cloud. We investigate four important factors of security awareness behaviour that should be considered when organisations intend to improve their security toward cloud computing environment based on awareness-focused programs. Finally we conclude that a well-structured awareness program that positively affect the level of self-efficacy, security practice care behaviour, security awareness technology behaviour and intention will improve the level of total information security in cloud computing environment